Systemic safety inequities for people with learning disabilities: a qualitative integrative analysis of the experiences of English health and social care for people with learning disabilities, their families and carers - Lauren Ramsey; Abigail Albutt; Kayley Perfetto; Naomi Quinton; John Baker; Gemma Louch; Jane O'Hara (BMC, 2022)
Abstract Background Failures in care for people with learning disabilities have been repeatedly highlighted and remain an international issue, exemplified by a disparity in premature death due to poor quality and unsafe care. This needs urgent attention. Therefore, the aim of the study was to understand the care experiences of people with learning disabilities, and explore the potential patient safety issues they, their carers and families raised. Methods Two data sources exploring the lived experience of care for people with learning disabilities were synthesised using an integrative approach, and explored using reflexive thematic analysis. This comprised two focus groups with a total of 13 people with learning disabilities and supportive staff, and 377 narratives posted publicly via the feedback platform Care Opinion. Results The qualitative exploration highlighted three key themes. Firstly, health and social care systems operated with varying levels of rigidity. This contributed to an inability to effectively cater to; complex and individualised care needs, written and verbal communication needs and needs for adequate time and space. Secondly, there were various gaps and traps within systems for this population. This highlighted the importance of care continuity, interoperability and attending to the variation in support provision from professionals. Finally, essential 'dependency work' was reliant upon social capital and fulfilled by paid and unpaid caring roles to divergent extents, however, advocacy provided an additional supportive safety net. Conclusions A series of safety inequities have been identified for people with learning disabilities, alongside potential protective buffers. These include; access to social support and advocacy, a malleable system able to accommodate for individualised care and communication needs, adequate staffing levels, sufficient learning disabilities expertise within and between care settings, and the interoperability of safety initiatives. In order to attend to the safety inequities for this population, these factors need to be considered at a policy and organisational level, spanning across health and social care systems. Findings have wide ranging implications for those with learning disabilities, their carers and families and health and social care providers, with the potential for international learning more widely.